The adoption of halal food supply chain towards the performance of food manufacturing in Malaysia - Fadhlur Rahim Azmi; Abu Abdullah; Mohammed Hariri Bakri; Haslinda Musa; Mailasan Jayakrishnan (Management Science Letters, 2018)
Halal industry in Malaysia provides a great opportunity for food manufacturers to expand their businesses, globally. However, the business has faced with some difficulties to improve performance due to complexity in halal supply chain. This paper studies the adoption of halal food supply chain (HFSC) factors on business performance among halal food manufacturers in Malaysia. Data were collected randomly from Halal Development Council (HDC) directory website. Using regres-sion analysis, 103 responses were analyzed to determine the effects of adoption factors of HFSC on business performance. The results indicate that the context of technological, organizational and environmental can improve business performance of halal manufacturer. Perceived benefits in the context of technological gives the best predictor on business performance. In the context of organizational, readiness provides the best predictor of business performance. Meanwhile, halal market demand in the context of environmental gives the best predictor of business performance. The paper examines business performance in food industry; however other industries in halal are not focused. The results provide some insights into business performance among halal industry in Malaysia.